Determinants of a pre-treatment model in achieving economic and environmental sustainability in membrane desalination - Lee, Man Djun; Sebastian Dayou,; Prashobh Karunakaran, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Feedwater pre-treatment plays a significant role in the production performance of water desalination operations. This study aims to formulate a pre-treatment model to evaluate the determinants in achieving economic and environmental sustainability. The research is oriented toward the goal of productivity and performance improvement in the water desalination process. The main objective of this study was to better understand the relationship between feedwater pre-treatment and demineralised water production. The secondary objective was to investigate the effect of an ultrafiltration membrane (UFM) on feedwater production performance. Case studies and literature review are included in this paper. Factors that potentially hinder the efficiency and reduce the load capacity of the desalination process include sand, high levels of ionic bond, biomass and colloid materials. These fouling factors could be eliminated efficiently from the feedwater during pre-treatment. Results demonstrated that the contribution of all inputs to achieve targeted pre-treated water quality (SDI < 3) was significant (p < 0.05) except for activated carbon. Investigations of the pre-treatment process have shown that the silt density index (SDI) is reduced by 45% using a UFM. Higher performance in water desalination was achieved through a higher efficiency in the removal of bacteria, sand, biomass and natural organic materials. Economic analysis showed that overall capacity utilization and operating performance had increased by 11%. This study concludes that quality pre-treatment is essential for achieving higher performance in membrane desalination operations.